What is the Issue with Internet Acceptance among Elderly Citizens? Theory Development and Policy Recommendations for Inclusive E‐Government - Niehaves, Björn; Plattfaut, Ralf (Electronic Government - 9th IFIP WG 8.5 International Conference, EGOV 2010, Lausanne, Switzerland, August 29 - September 2, 2010. Proceedings, 2010)
Digital divide is still a big topic in information systems and e-government research. In the past, several tracks and workshops on this topic existed. As information technology and especially the internet become more and more important governments cannot ignore the fact that elderly citizens are excluded from the benefits related to internet usage. Although e-Inclusion programmes and initiatives changed over the years and, moreover, although the amount of e-Inclusion literature is constantly growing, there is still no thorough understanding of potential factors influencing private internet usage. Hence, in this study we identify important influencing factors based on the literature on technology acceptance and digital divide. We develop a model based on these factors and test it against comprehensive survey data (n=192). Our theoretical model is able to explain more than 70 percent of the variation in private internet usage. We derive policy recommendations based on the results and discuss implications for future research.